Technological innovations and worker health: comparative study of the operation of furnaces in a red ceramic industry in the region of Cariri, Ceará (Research, Society and Development, 2022)
The technological innovations, fundamental to the industrial development, has influenced the human life and the work. In this context, this research sought to analyze the existence of risks in the operation of industrial furnaces, used in the process of burning tiles and bricks in a red ceramic industry located in the municipality of Milagres, Ceará. The objective was to identify how the technological innovation implemented in the ceramic furnaces can impact on the workers health and safety, how also in the preservation of social rights of that working class. The methodology have approach qualitative, through descriptive and comparative analysis, realized out from a case study. During the phase of data collect, on-site visits were shop floor to detail the production process of ceramic and, in particular, in the burn stage of the products. The evidence of this study corroborates that workers in this productive sector are exposed quotidian the several types of occupational risks. In technological terms, these problems could have already been solved and, therefore, the contribution of technological development was expected to result in an increase in product quality, increased productivity, fuel savings, reduction in pollutant emissions and, consequently, in greater operational safety.